PENGARUH KEBIJAKAN DEVIDEN, PROFITABILITAS,UKURAN PERUSAHAAN, RESIKO BISNIS, CASH HOLDING, KONTROL KEPEMILIKAN, DAN NON DEBT TAX SHIELD TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (PERIODE 2011-2014) - Nainggolan, Misco Valensi; Azlina, Nur; ', Julita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of dividend policy, profitability, company size, business risk, cash holding, ownership and control of non-debt tax shield on capital structure on companies listed in Indonesia Stock Exchange period 2011-2014.The sample used in this study is a company manufacturing consumer goods industry sub-sectors listed in Indonesia Stock Exchange in 2011-2014. This study usingpurposive sampling method to determine the sample so as to produce 27 sample companies. Data were analyzed using multiple linear regression method and descriptive statistics.The study found that in Parsial dividend policy have a negative impact but did not significantly influence the capital structure, profitability have a negative impact but not significant to capital structure, company size has no significant effect on the capital structure, Business Risk positive effect but not significant to the capital structure, cash holding no significant effect on the capital structure, ownership control but no significant negative effect on the capital structure, non-debt tax shield but no significant effect on the capital structure. The magnitude of the effect caused by the seven independent variables together against the dependent variable is 28.1%, while the remaining 71.9% is influenced by other variables not examined in this study.Keywords: Devidend policy, Profitability, Cash holding, Capital structure